A mixed-methods study of psychological distress following an environmental catastrophe: the case of the Hazelwood open-cut coalmine fire in Australia. Issue 2 (3rd March 2020) - Maybery, Darryl; Jones, Rebecca; Dipnall, Joanna F.; Berger, Emily; Campbell, Timothy; McFarlane, Alexander; Carroll, Matthew
ABSTRACT: Background and Objectives: This study assessed the psychological impacts of six weeks of smoke exposure from the 2014 Hazelwood open-cut coalmine fire in the Latrobe Valley, Victoria, Australia, between two and three years after the incident. Design and Methods: A cross-sectional survey of adults investigated outcomes for the most exposed community, Morwell ( n  = 3091), compared with a similar, but minimally exposed community, Sale ( n  = 960). Adopting a mixed-methods research approach, 26 interviews with Morwell residents further examined qualities of the experience. Results: Morwell residents scored significantly higher on the Impact of Event Scale – Revised (difference = 6.53; 95%CI: 5.37, 7.35, p  < 0.001) and Kessler 10-item general distress scale (difference = 1.69; 95%CI: 1.05, 2.33, p  < 0.001). More than two years after the mine fire, Morwell residents reported moderate levels of distress related to the incident. This impact was also evident in interviews, where intrusive thoughts were the most frequently reported symptom of posttraumatic stress. Furthermore, interviews highlighted the vulnerability of people with pre-existing mental health concerns. Conclusions: The elevated psychological distress apparent within the Morwell community over two years after an extended pollution event highlights the need to improve post-incident recovery responses to such events, particularly for supporting residents that are more vulnerable.